Efektivitas Penerapan Layanan Bimbingan Kelompok Teknik Sosiodrama Terhadap Perilaku Pubbing (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Phubbing behavior, which is the tendency to ignore those around us in favor of attention on social media, has become an increasing concern in the context of social interactions, especially among teenagers. This study aims to explore the impact of phubbing behavior on interpersonal communication among vocational school students. The research method used in this research is pre-experimental design with a one group pretest-posttest research design. The population of this research is SMK in Rembang. The sample taken was 10 students using simple random sampling technique. To overcome this problem, this research proposes the application of group guidance using sociodrama techniques as an alternative intervention. The results of the analysis show that group guidance using sociodrama techniques has a positive influence in improving interpersonal communication between students. The implication of this research is the importance of appropriate interventions in dealing with phubbing behavior among adolescents to improve the quality of interpersonal relationships and their psychological well-being.